Strategi Dakwah SALIMAH: Membangun Karakter Muslimah yang Tangguh - Muna Lutfiya Salma; Kayyis Fithri Ajhuri (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2024)
The Salimah Community (Muslim Brotherhood) is an organization that focuses on empowering Muslim women through religious, educational, and social programs. Established in 2012 in Nguntoronadi District, Wonogiri Regency, this community plays an important role in shaping the character of Muslim women. This study aims to analyze the role of Salimah in building the character of Muslim women through the da'wah approach and social activities. A qualitative descriptive approach was used in this study, with data collection through in-depth interviews, observations, and documentation studies. Data analysis was carried out using the triangulation method. The results of the study show that Salimah has succeeded in shaping the character of Muslim women through religious study programs, personality training, and social activities such as fundraising for orphans and parenting socialization. Salimah's da'wah strategy is designed in a structured manner, involves the active participation of members, and is evaluated periodically to increase its effectiveness. As a result, there is an increase in religious understanding, social solidarity, and awareness of the role of Muslim women in society. Salimah is not only a religious community, but also an agent of social change that contributes to the formation of individuals with Islamic character and a better society.